Infant orbital osteotomy with ultrasonic surgical unit: 2 Cases - Abdul Rahman, Shaifulizan; Alam, Mohammad Khursheed; Shaari, Ramizu; Awang, Mohamed Saufi (Japan International Cultural Exchange Foundation (JICEF), 2014)
Background: Nasoethmoidal encephaloceles are herniations of intracranial contents through the foramen cecum between nasal bone and nasal cartilage, and involve the ethmoid complex. Incidence of encephalocele is 1:5000 to 1:10000 live births, more common in females. Case presentation: We presented 2 cases, a baby girl born with congenital nasoethmoidal encephalocele and another with midline enchepalocele. The encephaloceles are classified according to the location and content. The most important is to return the cerebral components in to the cranial cavity along with amputation of dysplastic tissue and closured of bony defect. Conclusion: Consequently helping in planning the prompt surgical approach may prevent a range of complications such as developmental delay, cognitive deficits, and meningitis. The survival rate is good in anterior encephalocele as compared to the posterior encephalocele.